2020
DOI: 10.1158/1541-7786.mcr-19-1041
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial Carcinoma of the Bladder Induces Endothelial Cell Activation and Hypercoagulation

Abstract: Cancer related venous thromboembolisms (VTE) are associated with metastasis and reduced survival in patients with urothelial cancer of the bladder (UCB). Although previous reports suggest the contribution of tissue factor and podoplanin, the mechanistic linkage between VTE and bladder cancer cell derived molecules is unknown. Therefore, we compared distinct procoagulant pathways in four different cell lines. In vitro findings were further confirmed by microfluidic experiments mimicking the pathophysiology of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…qRT-PCR was performed as previously reported [47]. Briefly, Total RNA was extracted using the RNeasy Plus Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer's protocol and qRT-PCR was performed using the Reverse Transcription System and the GoTaq qPCR Master Mix (Promega, Heidelberg, Germany).…”
Section: Qrt-pcrmentioning
confidence: 99%
“…qRT-PCR was performed as previously reported [47]. Briefly, Total RNA was extracted using the RNeasy Plus Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer's protocol and qRT-PCR was performed using the Reverse Transcription System and the GoTaq qPCR Master Mix (Promega, Heidelberg, Germany).…”
Section: Qrt-pcrmentioning
confidence: 99%
“…Previously, we showed that platelets could be trapped at the vessel wall by ultralarge vWF fibres released from activated endothelial cells through a VEGF-A mediated signalling [26]. However, our previous research indicated that the SN of T24 cells was unable to instantaneously mediate the release of vWF from HUVECs [26]. Here, we measured the binding of platelets upon prolonged pre-treatment of the HUVECs (6 h) with T24 cell SN (Fig.…”
Section: Ubc Cell Induced Platelet Binding and Leukocyte Recruitmentmentioning
confidence: 80%
“…We measured platelet binding (platelet covered area) as an indicator of pro-thrombotic endothelial cell activation. Previously, we showed that platelets could be trapped at the vessel wall by ultralarge vWF fibres released from activated endothelial cells through a VEGF-A mediated signalling [26]. However, our previous research indicated that the SN of T24 cells was unable to instantaneously mediate the release of vWF from HUVECs [26].…”
Section: Ubc Cell Induced Platelet Binding and Leukocyte Recruitmentmentioning
confidence: 96%
“…Similarly, tumor cells have also been shown to secrete soluble factors that induce WPB exocytosis. For example, tumor secretomes derived from lung (A549) cells, prostate (PC3) cells, urothelial carcinoma (RT4) cells, colon cancer (HT‐29) cells, and melanoma (MV3, BLM) cells were able to promote VWF secretion from primary human ECs in vitro 32‐38 . Thus, tumor‐mediated VWF secretion from ECs is likely to contribute to the elevated plasma VWF:Ag reported in these patient cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tumor‐mediated VWF secretion from ECs is likely to contribute to the elevated plasma VWF:Ag reported in these patient cohorts. The biological mechanisms through which the tumor secretome induces EC activation is varied, but includes inflammatory cytokines (IL‐6 and −8), matrix metalloproteinases (MMP‐1 and MMP‐2), and angiogenic mediators (vascular endothelial growth factor A [VEGF‐A]) 32‐38 …”
Section: Introductionmentioning
confidence: 99%